A microbial perspective on the life‐history evolution of marine invertebrate larvae: If, where and when to feed. (14th March 2018) - Carrier, Tyler J.; Macrander, Jason; Reitzel, Adam M.
Abstract: The feeding environment for planktotrophic larvae has a major impact on development and progression towards competency for metamorphosis. High phytoplankton environments that promote growth and development also correlate with a greater abundance of environmental microbes and incidence of pathogenic microbes, making these habitats potentially risky for larvae. Trade‐offs between metabolic processes for growth and immune functionality have been described throughout the animal kingdom and may influence the life‐history evolution of marine invertebrate planktotrophic larvae. Specifically, larvae would be predicted to regulate time spent between these feeding environments to avoid potential incidences of microbial‐mediated mortality and/or dysbiosis. Using transcriptomic and microbiome data, we provide evidence for this trade‐off in larvae of the sea urchin Strongylocentrotus droebachiensis . When cultured in a well‐fed environment, larvae upregulate genes associated with metabolism while decreasing the expression of genes associated with immune function. At the same time, the associated bacterial community shifts towards a state of dysbiosis that is followed by mortality. To test whether the environmental microbiota is a selective force on if, where and when planktotrophic larvae should feed, we conclude by presenting a strategy for determining the specific interactions of larvae and microbes at a scale representative of their pelagic environment.